Photoaffinity labeling of protein O-Mannosyltransferases of the PMT1/PMT2 subfamily - Loibl, Martin; Strahl, Sabine (Glycosyltransferases, 2013)
Protein O-mannosylation is initiated at the endoplasmic reticulum (ER) by dolichyl phosphate-mannose: protein O-mannosyltransferases (PMTs). PMTs are members of the glycosyltransferase (GT) C superfamily. They are large polytopic integral membrane proteins located in the ER membrane. PMTs utilize dolichyl phosphate-activated mannose as sugar donor. Glycosyltransfer of mannose to serine and threonine residues of nascent polypeptides leads to an inversion of the stereochemistry of the glycosidic bond. Here, we describe photoaffinity labeling of yeast Pmt1p using a photo-reactive probe that is based on the artificial mannosyl acceptor peptide YATAV. Due to the high homology of PMTs, this method can also be applied to study PMT1 and PMT2 subfamily members from fungi other than baker’s yeast.
Gesehen am 15.05.2017